Silver and Copper Coating Effects on Surface Morphology, Crystal Structure and Corrosion Behavior of NiTinol Shape Memory Alloy Plate - Say, Yakup; Kanca, Muhammed Sait; Kok, Mediha (Springer India, 2023)
NiTinol alloy has recently been in high demand in biomaterials applications due to its excellent superelasticity and shape memory properties. This demand has increased the studies on improving the negative properties of the NiTinol alloy, even if it is less. In this study, it was aimed to coat the nickel element in the NiTi alloy with biocompatible elements in order to prevent it from secreting its toxic effect after its implantation into the body. In accordance with this purpose, NiTi shape memory alloys were coated with silver and copper element by using thermal evaporation system, and the surface morphology of the alloys after coating was investigated by SEM-EDX (Scanning Electron microscope), and AFM (Atomic force Microscope). After the measurements, it was observed that the coating was successful and homogeneously distributed on the entire surface of the alloy. In addition, an important and positive result was that, the roughness value of the NiTi alloy was decreased with the coating. The change in the crystal structure of the uncoated and coated NiTi alloy was evaluated using an X-ray device, and it was observed that the silver and copper element peaks were formed along with the B2 phase, which is the main phase of the NiTi alloy. In order to examine the effect of coating on the biocompatibility of NiTi alloy, electrochemical test was performed by rapid measurement method in simulated body fluid and corrosion behavior was investigated. According to these experiments, it was concluded that silver plating is more successful in term of biocompatibility than copper coating.
Keywords: Corrosion; Surface morphology; Coating; Thermal evaporation system